Exploring the Etiological Evidences at Avascular Necrosis of Femoral Head by Investigative Approaches of Histopathology, Clinical Assessment and Radiology - Kiran Saoji1 , Sandeep Shrivastava2 , Arvind Bhake3 , Aditya Kekatpure4 , Sunil Nikose5 , Aashay Kek (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background- The avascular necrosis of the femoral head includes interference of the blood flow to thefemoral head. This ischemia leads to death of the bone cells and bone marrow followed by the collapse ofthe bone femoral head, which finally leads to the destruction of the bone tissue and arthritis,Objectives:1. Histopathological analysis of the tissue obtained after core biopsy or sections of head after head excisionwhile doing Arthroplasty.2. Correlation between histopathological evidence with clinical and radiological findings.Methodology: The tissue will be sampled from site of AVN during surgical procedure that is Coredecompression or hip arthroplasty. Tissue material obtained will be transfered to regular histological fixativeof 10 % formalin. It will be fixed for a day, later to be reprocessed for decalcification. Formalin fixed tissuewill be subjected for treatment of running water to remove excess of formalin. Later the tissue will beexamined for its gross appearance of any changes of autolysis The process of decalcification adopted forpresent work is chemical one. The decalcification tissue will be subjected for histokinette cycle. The tissueis now ready for paraffin block. These paraffin blocks will be subjected to microtomy for obtaining 5 micromilimeter sections. These paraffin sections will be stained for H/E and Van. Giesson stain. Histopathologicalassessment of the tissue will be carried out for the evidence and grading of avascular necrosis.Expected Results: Correlation between histopathological evidence with clinical and radiological findings.Conclusion: This study will be helpful in developing Histopathological staging in correlation with clinical,radiological findings.